2009
DOI: 10.1183/09031936.00065809
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of cell adhesion in airway epithelial cell types using electric cell-substrate impedance sensing

Abstract: Research on epithelial cell lines and primary epithelium is required to dissect the mechanisms underlying the structural abnormalities in airway epithelium observed for respiratory diseases, including asthma and chronic obstructive pulmonary disease.The novel electric cell-substrate impedance sensing technique was used to monitor cell adhesion/spreading, barrier function and wound healing. Primary bronchial epithelium was compared with airway epithelial cell lines 16HBE14o-, BEAS-2B, NCI-H292 and A549.BEAS-2B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 21 publications
(26 reference statements)
5
114
0
Order By: Relevance
“…Using this type of wounding, the epithelial monolayer is able to recover within a few hours, as a result of cell migration/ spreading, and not from proliferation [19]. Barrier function of the 16HBE cells completely recovered within 2 h ( fig.…”
Section: Cse Delays Epithelial Regeneration and Reconstitution Of Celmentioning
confidence: 95%
See 3 more Smart Citations
“…Using this type of wounding, the epithelial monolayer is able to recover within a few hours, as a result of cell migration/ spreading, and not from proliferation [19]. Barrier function of the 16HBE cells completely recovered within 2 h ( fig.…”
Section: Cse Delays Epithelial Regeneration and Reconstitution Of Celmentioning
confidence: 95%
“…Addition of CSE induced a substantial transient fall in low-frequency resistance, the most sensitive parameter to monitor barrier tightness [18,19]. Resistance levels started to decline immediately, with a maximal effect between 4 and 6 h (maximal mean¡SEM decrease 26¡3%; n55), followed by a slow return to control values over ,15 h ( fig.…”
Section: Cse Induces a Transient Decrease In Electrical Resistance Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The inflammation resulting from cigarette smoke exposure, subsequently, the released agents from the inflammatory cells, and the protease-antiprotease imbalance in the lungs lead to the damage of the alveolar epithelium (2,6). The cell death in the alveolar epithelium cells has been shown in the experimental studies where pulmonary emphysema was induced by several substances such as cigarette smoke, elastase, and papain (7,14,16). It has been suggested that alveolar epithelial damage occurs irreversibly and that the repair of alveolar epithelium cannot be done in the pulmonary emphysema (7).…”
Section: Discussionmentioning
confidence: 99%